Population happiness, life satisfaction and well-being in transitional societies - Kizilova, Kseniya; Haerpfer, Christian; Kizilov, Oleksandr (Ukrainian Sociological Journal, 2017)
Current paper deals with the analysis of dynamics of the level of well-being in the countries of Post-Soviet Eurasia who in 1991 entered the path of democratic transition. The paper focuses on subjective indicators of well-being, among them general life satisfaction and feeling of happiness. These indicators are used for calculation of the index of subjective wellbeing. The data used for analysis comprises from the World Values Survey wave 1 (1981-1984) to wave 6 (2010-2014). The following 10 countries of Post-Soviet Eurasia are included into the analysis: Armenia, Azerbaijan, Belarus, Georgia, Moldova, Kazakhstan, Kyrgyzstan, Russia, Ukraine and Uzbekistan. The paper provides overview of dynamics of the level of subjective well-being in the mentioned countries in period of transition. Comparative overview of the level of subjective well-being in Post-Soviet Eurasia and other world regions is presented. Multivariate analysis is used to determine the main factors influencing subjective well-being in different parts of the world.